DNA in serum extracellular vesicles is stable under different storage conditions. Issue 1 (December 2016) - Jin, Yang; Chen, Keyan; Wang, Zongying; Wang, Yan; Liu, Jianzhi; Lin, Li; Shao, Yong; Gao, Lihua; Yin, Huihui; Cui, Cong; Tan, Zhaoli; Liu, Liejun; et al.
Abstract Background Extracellular vesicles (EVs), including exosomes, microvesicles, and apoptotic bodies, can be secreted by most cell types and released in perhaps all biological fluids. EVs contain multiple proteins, specific lipids and several kinds of nucleic acids such as RNAs and DNAs. Studies have found that EVs contain double-stranded DNA and that genetic information has a certain degree of consistency with tumor DNA. Therefore, if genes that exist in exosomes are stable, we may be able to use EVs genetic testing as a new means to monitor gene mutation. Methods In this study, EVs were extracted from serum under various storage conditions (4 °C, room temperature and repeated freeze-thaw). We used western blotting to examine the stability of serum EVs. Then, we extracted DNA from EVs and tested the concentration changing under different conditions. We further assessed the stability of EVs DNA s using polymerase chain reaction (PCR) and Sanger sequencing. Results EVs is stable under the conditions of 4 °C (for 24 h, 72 h, 168 h), room temperature (for 6 h, 12 h, 24 h, 48 h) and repeated freeze-thaw (after one time, three times, five times). Also, serum DNA is mainly present in EVs, especially in exosomes, and that the content and function of DNA in EVs is stable whether in a changing environment or not. We showed that EVs DNA stayed stable for 1 week at 4 °C, 1 day at room temperature and after repeated freeze-thaw cycles (less than three times). However, DNA from serum EVs after 2 days at room temperature or after five repeated freeze-thaw cycles could be used for PCR and sequencing. Conclusions Serum EVs and EVs DNA can remain stable under different environments, which is the premise that EVs could serve as a novel means for genetic tumor detection and potential biomarkers for cancer diagnostics and prognostics.